PEMBELAJARAN MENYIMAK APRESIATIF CERITA PENDEK DENGAN STRATEGI BELAJAR KOOPERATIF - Nurhidayati Nurhidayati (LITERA, 2011)
This study aimed to describe the improvement in the learning of appreciative short-story listening through a cooperative learning strategy. It employed an action research design. The data were those of the implementation of the learning of appreciative listening, which included pre-listening, listening, and post-liste ning stages. The data collecting instruments consisted of an observation guide, accompanied by a tape recorder and field notes, and a rubric for the analysis of the appreciative listening results. The findings showed that the cooperative learning strategy was effective in the whole learning process of listening. The students attained a mean of 91.6 (very good) at the end of Cycle I and a mean of 93 (very good) at the end of Cycle II.